Early Hair Regrowth With Adjunctive Secretome Therapy in Severe Patchy Alopecia Areata: Pertumbuhan Rambut Dini dengan Secretome Adjuvan pada Alopecia Areata Berat - Zada Febrial Effendy; Anang Silahudin; Dhyah Aksarani Handamar; Shinta Dewi Rahmadhani Soetojo (Academia Open, 2026)
General Background: Alopecia areata is a non-scarring immune-mediated hair loss disorder with an unpredictable course and frequent relapse. Specific Background: Corticosteroids remain standard treatment for active disease, but responses may be inconsistent when scalp involvement is extensive, while clinical evidence for mesenchymal stem cell-derived secretome remains limited. Knowledge Gap: Reports combining MSC-derived secretome with standard corticosteroid therapy in severe patchy alopecia areata while objectively tracking Severity of Alopecia Tool scores remain scarce. Aims: This case report described the early clinical course of a 23-year-old man with severe patchy alopecia areata and an estimated baseline SALT score of 73 who received intralesional triamcinolone, oral methylprednisolone, topical mometasone, and adjunctive secretome. Results: After one month, hair density increased with visible vellus and early terminal hairs, while the estimated SALT score decreased from 73 to 55, representing approximately 25% less scalp involvement. No new patches, local complications, or reported systemic adverse effects were observed. Novelty: The case provides objectively tracked early SALT changes during a corticosteroid-based multimodal regimen incorporating cell-free secretome. Implications: The findings warrant controlled prospective studies with standardized preparations and longer follow-up because the concurrent treatments prevent attribution of the observed response to secretome alone. Highlights: Estimated scalp-loss scoring declined from 73 to 55 within one month. Vellus and terminal hairs became visible across previously bald scalp regions. No treatment-related local or systemic adverse effects were observed during follow-up. Keywords: Alopecia Areata, Secretome, Intralesional Triamcinolone, Corticosteroids, Regenerative Medicine